Experiência e pesquisa: racismo, relações de poder, educação e arte - Figueira, Michele Spall (2017)
The research proposed to pedagogically problematize racism and power relations from discursive practices in the space of art classes, working with students of a class of 9th grade elementary school Aracy Barreto Sacchis Municipal School during the first semester This investigation is characterized as educational ethnographic, and to analyze the data, I used the analysis of the Foucaultian discourse. Access to the sources for data collection and production during the period of investigation occurred in the pedagogical interaction. In defining the theme, my teaching commitment was mainly to maintain an investigative and guiding stance of the entire process. The meetings and activities carried out in the school space were recorded in field diary, photography, transcribed reports. On the part of the collaborating students of the research this data was provided in speeches, writings and visual productions. In this way, the data to be analyzed were analyzed by Foucault-inspired discourse (1999) and Foucault's analysis of discursive practices that raise two important points to be explored: the discourse production scenario and the effects of the will of truth and power of these discourses. The data cut for analysis purposes were the manifestations of the subjects, which constitute the materiality of their discursive practices, which will be disintegrated in the effort to appreciate the research question. The main trigger of this research is racism taking its place in experience, art, culture, society permeated by the conditions of possibility associated with power. Regarding the selection of authors, I emphasize that the cast was determined according to the research ideas, giving vigor, flexibility and the possibility of firing multiplier of other ideas. Foucault (1997, 1999, 2008, 2016), Fischer (2002, 2015), Veiga-Neto (2014, 2016), Skidmore 2012, Benjamin 1987, Larrosa 2015, Hernandez 1998, (2010, 2016), Moraes (2004, 2016) are constant presences in the development of the work, and of course, I must emphasize that I made a cut in these names because the research does not embrace the totality of their works. The importance of this study is in the production of new places for thinking and thinking, in the visual production that manifests this thinking materially, in the production of experiences with knowledge and that generate knowledge, in the production of a relation of teaching and mutual learning and simultaneous between teacher-mediator-researcher and student-researchers, in the production of multiple triggers for a productive education and not (only / only) reproducer of a discourse that reinforces regimes and truths. Working with contemporary visual languages was a lever that launched each of us into the immensity of becoming, and we needed to produce it added to the complexity of the themes of racism and power. The (self) productive potentiality was the main engine and end of this proposal in education and art. I do not propose with this study revolutions, but movements that can be significant in the experience with art in the scholar scope in the student and teacher sphere.